Participatory research and development for sustainable agriculture and natural resource management a sourcebook - Gonzalves, Julian (International Potato-Center Users' Perspectives With Agricultural Research and Development International Development Research Centre, 2005)
Contains PDF format of the material. Installation file is also included.